Brand Image Memediasi Kualitas Produk dan Harga Terhadap Keputusan Pembelian - Parida Meida Fera; Erny Amriani Asmin; Rachmat Gunawan (FEB Universitas Maritim Semarang, 2023)
The purpose of this study wasto identify and analyze the role of product image to inform product quality and purchasing decisions for aqua 600ml mineral water in Sukabumi District. The survey wan conducted amon 97 respondents using purposive sampling technique based on the following criteria:1) consumers who purchased at least on aqua 600ml product and 2) product choice. Customers must be at least 17 years old andold enough tocompletethe survey. The questionnaire was tested with validity, realibilty andclassical acceptance tests.the analitysis method used in this research is descritivemethod and validation through quantitative method. Data analysis techniques were carriedout by path analysis and sobeltest using SPSS for windows.thus, product quality has a positive and significant effect on brand image, price has a positive and significant effet on brand image, product quality has no and insignificant effect on purchasing decisions and price has a positive effect and significant on purchasing decisions. Brand image affects product quality on purchasing decisions. Brand image can influence price in purchasing decisions.